Scoping Review: Gejala Klinis Pasien Covid-19 dengan Koinfeksi Tuberkulosis - Muhammad Gilang Wicaksana; Winni Maharani; Lisa Adhia Garina (Bandung Conference Series: Medical Science, 2023)
Abstract. Coronavirus disease 2019 (COVID-19) and tuberculosis (TB) are infectious diseases that can be transmitted by droplets. The clinical manifestations of COVID-19 disease can worsen if there are comorbidities, one of which is TB disease. Epidemiologically, COVID-19 and TB are two diseases with a very high incidence and are a global health problem. The study aims to analyze the impact of TB co-infection on the clinical symptoms of COVID-19 patients. This research uses the scoping review method using scientific articles published in three databases SciencDirect, SpringerLink, and Pubmed in 2019-2022. In the data search, 2,773 articles were obtained with the acquisition of 404 articles that met the inclusion criteria and 6 articles after PICOS analysis was carried out. The results showed that the dominant clinical symptoms that occurred at all ages were respiratory symptoms, fever, cough, chest pain, and dyspnea. In addition, there are additional clinical symptoms in pediatric patients in the form of nausea, diarrhea, headache, tachypnoea, and altered sensorium (impaired awareness, attention or difficulty focusing thoughts). Other results describe an increase in the release of cytokines (IFN-γ, TNF, IL-4, and IL-13) against both pathogens resulting in a "cytokine storm" that can affect the clinical symptoms of patients. The conclusion of this study shows that COVID-19 and TB infection have an adverse clinical impact on patients. Abstrak. Penyakit virus corona atau Corona virus disease (COVID-19) dan tuberkulosis (TB) merupakan suatu penyakit menular yang dapat ditransmisikan melalui droplet. Manifestasi klinik penyakit COVID-19 dapat memburuk bila terdapat komorbiditas salah satunya adalah penyakit TB. Secara epidemiologi penyakit COVID-19 dan TB merupakan dua penyakit dengan angka kejadian sangat tinggi yang menjadi masalah kesehatan dunia. Penelitian ini bertujuan untuk menganalisis dampak dari koinfeksi TB terhadap gejala klinis pasien COVID-19. Penelitian ini menggunakan metode scoping review menggunakan artikel ilmiah yang dipublikasikan pada tiga database SciencDirect, SpringerLink, dan Pubmed pada tahun 2019-2022. Pada pencarian data didapatkan 2,773 artikel dengan didapatkan 404 artikel yang sesuai dengan kriteria inklusi dan 6 artikel setelah dilakukan analisis PICOS. Hasil penelitian menunjukkan gejala klinis yang dominan terjadi pada semua usia adalah gejala saluran pernapasan, demam, batuk, nyeri dada, dan dispnea. Selain itu terdapat gejala klinis tambahan pada pasien anak berupa mual, diare, nyeri kepala, takipnea, dan gangguan system saraf seperti gangguan kesadaran, perhatian atau kesulitan memfokuskan pikiran. Hasil lain menggambarkan peningkatkan pengeluaran sitokin (IFN-γ, TNF, IL-4, dan IL-13) untuk melawan kedua patogen sehingga mengakibatkan “cytokine storm” yang dapat memperburuk gejala klinis pasien. Simpulan penelitian ini menunjukkan koinfeksi COVID-19 dan TB memperburuk dampak klinis pada pasien.